2019
DOI: 10.1016/j.amjcard.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Sitting on Peripheral and Central Vascular Health

Abstract: Prolonged, uninterrupted sitting negatively impacts markers of peripheral vascular health, particularly, vasodilatory function of leg arteries. Whether sitting can similarly impact measures of central vascular health, as well as overall leg vasoreactivity (i.e., vaso-dilatory and vasoconstrictor function) remains unknown. To address this, measurements were made in relatively healthy participants (i.e., free of overt disease; n = 20, age = 26 § 7; body mass index = 30 § 7 kg/m2; 7 female) pre, during and post 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
132
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(147 citation statements)
references
References 31 publications
10
132
5
Order By: Relevance
“…As such, further study is warranted to determine whether the findings are generalizable to other populations. Second, we recently reported that, compared to women, men exhibit a greater increase in aortic arterial stiffness following prolonged sitting (Credeur et al, ). While we were not adequately powered to determine sex interaction effects, we cannot rule out that sex differences existed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As such, further study is warranted to determine whether the findings are generalizable to other populations. Second, we recently reported that, compared to women, men exhibit a greater increase in aortic arterial stiffness following prolonged sitting (Credeur et al, ). While we were not adequately powered to determine sex interaction effects, we cannot rule out that sex differences existed.…”
Section: Discussionmentioning
confidence: 96%
“…Considering this is the first study to simultaneously assess cerebral perfusion and executive function during acute prolonged sitting, a homogenous group of young, healthy adults was recruited to minimize the confounding influence of age and cardiometabolic abnormalities. In a similar population, our group previously reported a positive relationship between cerebral perfusion and executive function in young adults during cycling exercise (Faulkner et al, ), A 3‐hr sitting duration was selected following previous work demonstrating this duration to result in negative impairments to peripheral and central vascular health (Credeur et al, ). Calf raise exercise was selected because it engages the muscle pump, one of the primary mechanisms ensuring venous return.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies can investigate environmental correlates of other types of sedentary behaviour. Moreover, evidence suggests that it is not just too much sitting, but also prolonged bouts of sitting which are deleterious to health (Credeur et al 2019;Dempsey et al 2018). Further research is needed to identify how environmental attributes may support breaking prolonged bouts of sitting.…”
Section: Discussionmentioning
confidence: 99%
“…10 A negative effect on peripheral and central vascular health was found when individuals remained in a seated position for greater than 3 hours. 37 In 2012, a professional esports athlete had a deep vein thrombosis, and treatment was delayed because he was unaware that leg pain could indicate a life-threatening condition. Survey data have also demonstrated that more than 40% of esports athletes do not participate in any kind of physical activity, 10 which signals a high prevalence of exercise deficit disorder in this population.…”
Section: Metabolic Dysregulationmentioning
confidence: 99%